Evaluation of growth and survival of snakehead (Channa striatus bloch.) in captive condition - Mohd Pazai, Afzan Muntaziana (2014)
Growth and survival of endangered snakehead Channa striatus were investigated at different diets, feeding frequencies and stocking densities under captive rearing condition. The first experiment was carried out on C. striatus fry using selected fresh diets like as bloodworm, trash fish and Acetes shrimp. The fry fed with trash fish showed significantly higher (p < 0.05) weight gain percentage (376.50 ± 20.74 %) than those fed with Acetes shrimp (233.05 ± 10.18 %) and bloodworm (199.08 ± 17.25 %). Fry fed with trash fish also showed the best SGR value (6.24 ± 0.17 % day-1) followed by Acetes shrimp (4.81 ± 0.12 % day-1) and then bloodworm (4.33 ± 0.22 % day-1). The best FCR value (3.63 ± 0.27) was found in fish fed with trash fish compared to those fed with Acetes shrimp (7.41 ± 0.88) and bloodworm (11.48 ± 1.51). The second experiment was conducted to observe the variation of growth performance of C. striatus fry fed with commercial pellet and fresh trash fish. Three treatments were used in this experiment: trash fish (T1), commercial pellet (T2) and combination of trash fish and pellet (T3). The highest weight gain percentage (539.70 ± 33.67 %) was observed in T3, followed by T2 (475.77 ± 43.33 %) and T1 (189.46 ± 40.48 %). Significantly higher SGR was in T3 (5.30 ± 0.15 % day-1), than in T2 (4.99 ±0.21 % day-1) and T1 (3.01 ± 0.40 % day-1) respectively. The highest survival was observed in T3 (96.11 ± 1.83 %), followed by T2 (95.00 ± 2.59 %) and T1 (80.56 ± 6.54 %) respectively. The feeding frequency experiment was carried out using pellet that contained 44% protein for 42 days. The fry were fed at 6 % of body weight daily at 2, 4, 6 and 8 times/day. The result showed significant (p < 0.05) differences in the weight gain (%) among the treatments where 2 times/day yield the highest value (316.23 ±36.94 %). SGR was also exhibited significant (p < 0.05) difference among the feeding frequency treatments and ranged from 2.64 to 3.37 % day-1. The highest survival percentage was found in the fry fed 2 times/day (100.00 ± 0.00 %) while, the lowest was found in fry fed 8 times/ day (80.00 ± 0.00 %). The final experiment was on the effect of different stocking density of C. striatus in captivity. There were three treatment of stocking density in this experiment which were 20 (T1), 30 (T2) and 40 (T3) individual/m2. The final mean total length was significantly higher (p < 0.05) in T1 which was 17.70 ± 0.21 cm compared with T2 (16.55 ± 0.18 cm) and T3 (15.97 ± 0.21 cm). There was significant difference (p < 0.05) in weight gain percentage. The weight gain percentage in T1, T2 and T3 were 2262.990 ± 300.159, 2693.393 ± 298.070 and 1860.130 ± 77.614 % respectively. There were no significant different (p > 0.05) in SGR in T1 (1.55 ± 0.01 % day-1) and T2 (1.57 ± 0.05 % day-1) however both treatments were significantly difference with T3 (1.41 ± 0.01 % day-1). There was no significant different (p > 0.05) in FCR in all treatments used. The estimated gross and net production was higher in T3 (1775.79 g/m2), followed by T2 (1498.56 g/m2) and T1 (1111.08 g/m2). A similar trend was also found in net production among all the treatments. In conclusion, commercial pellet was the most suitable for C. striatus fry to promote better growth, weight gain and survival. Feeding frequency of 2 times/day was the optimum frequency for growth and survival of C. striatus. In term of growth performance, 20 individual/m2 was the most suitable stocking density. In term of production, 40 individual/m2 was the most suitable stocking density under a monoculture system in tank.